Effect of sample locations on computation of the exact scalar diffraction field (in English) [Örnekleme yerleri̇ni̇n skalar kirinim deseni̇ni̇n doǧru hesaplanmasindaki̇ etki̇si̇ (Türkçe)] - (:unkn) unknown (My University, 2012)
Computer generated holography is one of common methods to obtain three-dimensional visualization. It can be explained by behavior of propagating waves and interference. To calculate the scalar diffraction pattern on a hologram, there are myriad of algorithms in the literature. Some of them employ several approximations, so the calculated fields may not be the exact scalar diffraction field. However, there are algorithms to compute the exact scalar diffraction field with some limitations on the distribution of the given samples over the space. These algorithms are based on "field model" approach. The performance of an algorithm, based on field model, is investigated according to the distribution of given samples over the space. From the simulations, it was observed that the cumulative information provided by the given samples has to be enough to solve the inverse scalar diffraction field. The cumulative information can be increased by having more samples, but there are some scenarios that differential information obtained from the given samples can be infinitesimal, thus the exact diffraction field may not be computed. © 2012 IEEE.